2004
DOI: 10.1002/aoc.647
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of natural and cultured mussels (Mytilus galloprovincialis) from the northern Adriatic Sea by tributyltin and dibutyltin compounds

Abstract: The levels of tributyltin (TBT) and dibutyltin (DBT) compounds were measured by gas chromatography ion-trap mass spectrometry (GC-MS/MS) in natural and cultured mussels (Mytilus galloprovincialis) from the northern Adriatic Sea in spring 2003. The highest (725 ng g −1 dry weight) and lowest levels (198 ng g −1 dry weight) of butyltins (TBT + DBT) were found in native mussels from the Lagoon of Venice, with the higher values being detected in specimens collected next to a dockyard and the lower values in specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
7
2
Order By: Relevance
“…Probably the high concentrations found in autumn-winter were rather due to shipping maintenance activities, a very common practice in this period, than to the high maritime traffic of the summer. 1 Concentrations modified using the conversion factors reported in "Material and methods" Butyltin concentrations found in M. galloprovincialis during the spring-summer period in the area of Chioggia (TBT=528-986, DBT=294-678 ng g −1 d.w., as cations) were higher than those reported in Boscolo et al (2004) who obtained TBT and DBT concentrations of 124-597 and 74-128 ng g −1 d.w. as cation, respectively, in two lagoon sites close to Chioggia in 2003. As reported by Cáceres-Martínez and Figueras (1998), who studied reproductive cycles of M. galloprovincialis in the Ria de Vigo, spring conditions (i.e.…”
Section: Resultscontrasting
confidence: 74%
“…Probably the high concentrations found in autumn-winter were rather due to shipping maintenance activities, a very common practice in this period, than to the high maritime traffic of the summer. 1 Concentrations modified using the conversion factors reported in "Material and methods" Butyltin concentrations found in M. galloprovincialis during the spring-summer period in the area of Chioggia (TBT=528-986, DBT=294-678 ng g −1 d.w., as cations) were higher than those reported in Boscolo et al (2004) who obtained TBT and DBT concentrations of 124-597 and 74-128 ng g −1 d.w. as cation, respectively, in two lagoon sites close to Chioggia in 2003. As reported by Cáceres-Martínez and Figueras (1998), who studied reproductive cycles of M. galloprovincialis in the Ria de Vigo, spring conditions (i.e.…”
Section: Resultscontrasting
confidence: 74%
“…In the same way, initial differences in CI had no significant effect on the differences in CI obtained during the culture between mussel populations. Condition index has been used widely in growth studies as well as in research specifically related to pollution incidence on bivalve molluscs Guolan and Yong, 1995;Dame, 1996;Hummel et al, 1996;Modassir and Ansari, 2000;Leung and Furness, 2001;Amiard et al, 2004;Boscolo et al, 2004;Duquesne et al, 2004;Pampanin et al, 2005). In our experimental mussel cultures, despite occasional lower CI values for Pindo mussels, there was no clear pattern that persisted for the entire test period.…”
Section: Discussionmentioning
confidence: 65%
“…CI integrates growth parameters in shell and tissue weights, and is influenced by similar environmental and endogenous factors to tissue dry weight. However, it has been reported that CI is a weak indicator because it is not sensitive to low concentrations of pollutants (Guolan and Yong, 1995;Hummel et al, 1996;Leung and Furness, 2001;Amiard et al, 2004;Boscolo et al, 2004;Duquesne et al, 2004;Pampanin et al, 2005). CI variability is usually attributed to changes in food availability or the gametogenic cycle (Hummel et al, 1996;Amiard et al, 2004;Pampanin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies analyzing BTs used gas chromatography with flame photometric detection (GC-FPD) 10,16 and gas chromatography coupled to tandem mass spectrometry (GC-MS/MS). [17][18][19] In Brazil, some recent studies have used gas chromatography with pulsed flame photometric detection (GC-PFPD) to analyze BTs in both biotic and abiotic samples. 4,[20][21][22] For analysis of BTs by GC, it is necessary a derivatization step, for which the main used agents are Grignard reagent and sodium tetraethylborate.…”
Section: Introductionmentioning
confidence: 99%